INSTILLING RELIGIOUS AND MORAL VALUES IN CHILDREN THROUGH HABITUATION METHODS IN THE FAMILY - Nurdini, Nia Malindo (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to describe the inculcation of religious and moral values in children aged 5–6 years through the habituation method in families in Lakitan. This type of research uses descriptive and qualitative research. Collecting data using observation, interviews, and documentation The data analysis technique was carried out using data triangulation techniques. The results of this study indicate that the inculcation of religious and moral values in children aged 5–6 years is done through the habituation method in the family by teaching religious values, independence, courtesy, and then good things through the habituation process. Factors supporting the development of religious and moral values in early childhood are the attention of parents to teaching children religious and moral values and children's obedience to parents. Meanwhile, the inhibiting factors for the development of religious and moral values in early childhood are environmental conditions that can have a negative influence on children, both from words, attitudes, and ways of dressing that are not good, and polite and the lack of parents giving an example to children because of the time parents have with very few children.